Retroperitoneal Primary Yolk Sac Tumour in Adult Male - Bindu, Sudha; K, Santhosh Reddy; Kumari, Vijaya; Chandra, Suman (Indian Journal of Case Reports, 2017)
Yolk sac tumour also called as endodermal sinus tumour is a malignant germ cell tumour. Extra gonadal germ cell tumours are very rare. The most common extra gonadal site is mediastinum. Retroperitoneum is the second most common site of occurence. We report a case of a primary extragonadal yolk sac tumour in an adult male who presented with abdominal pain, Imaging showed a very large retroperitoneal mass. Histopathology of the biopsied specimen showed it as a Yolksac tumour.